Antecedents of teenage pregnancy from a 14-year follow-up study using data linkage - Stanley Fiona J; Lawrence David; Mitrou Francis; Gaudie Jennifer; Silburn Sven R; Zubrick Stephen R (BMC Public Health, 2010)
Abstract Background Many western nations continue to have high rates of teenage pregnancies and births, which can result in adverse outcomes for both mother and child. This study identified possible antecedents of teenage pregnancy using linked data from administrative sources to create a 14-year follow-up from a cross-sectional survey. Methods Data were drawn from two sources - the 1993 Western Australian Child Health Survey (WACHS), a population-based representative sample of 2,736 children aged 4 to 16 years (1,374 girls); and administrative data relating to all their subsequent births and hospital admissions. We used weighted population estimates to examine differences between rates for teenage pregnancy, motherhood and abortion. We used Cox proportional hazards regression to model risk for teenage pregnancy. Results There were 155 girls aged less than 20 years at the time of their first recorded pregnancy. Teenage pregnancy was significantly associated with: family type; highest school year completed by primary carer; combined carer income; whether the primary carer was a smoker; and whether the girl herself displayed aggressive and delinquent behaviours. An age-interaction analysis on the association with aggressive and delinquent behaviours found that while girls with aggressive and delinquent behaviours who were older at the time of the survey were at highest risk of teenage pregnancy, there was elevated risk for future teenage pregnancy across all ages. Conclusions Our findings suggest that interventions to reduce teenage pregnancy rates could be introduced during primary school years, including those that are focused on the prevention and management of aggressive and delinquent behaviour.